(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The present paper highlights the results of pedagogical research conducted at the Architectural Department in the Kamianets-Podilskyi Professional College of Construction, Architecture and Design. The study considers the vocational pre-higher education students’ perceptions of various graphic works in drawing and descriptive geometry in the context of graphic work features, and understanding the significance of drawing works for the formation of a future specialist in the construction industry. Students were suggested to fill in the forms with a list of the curriculum topics and give grades according to three criteria: usefulness for the future profession, the complexity of the graphic work and the engagement in performing the task.Research results provide problem-solving solutions related to teaching methodology of such disciplines as "Technical Drawings", "Drawings and Basics of Descriptive Geometry" and "Descriptive geometry".Based on research findings, the recommendations concerning teaching and increasing interest in educational material can be made. It has been found that certain topics do not arouse much interest in students, so we recommend improving students' motivation in the classroom by employing engaging tasks, taking into account the peculiarities of perception and attention when studying these topics. The topics that are difficult to master according to students' responses require more hours for studying, and the topics that students consider least useful should be reviewed, reformatted, or even excluded from the program.